The Effect of Work Discipline and Work Environment on Work Engagement with the Mediation of Work Motivation During Work From Home - Hans Christian Samosir; Dewi Susita; Corry Yohana (Siber Nusantara of Economic and Finance Review, 2025)
The shift in working patterns due to the pandemic and the digital era has posed new challenges for organizations in maintaining employee engagement. This study aims to analyze the effect of work discipline and work environment on work engagement, with work motivation as a mediating variable among employees of XYZ Bank during the implementation of remote work (Work From Home/WFH). The research applied a quantitative explanatory design using the PLS-SEM approach. The sample size was calculated using the Taro Yamane formula, resulting in 162 employees from various departments at XYZ Bank as respondents. Data were collected through an online questionnaire with indicators that have been tested for validity and reliability. The findings revealed that work discipline significantly affects both motivation and work engagement. Similarly, the work environment also has a significant effect on motivation and engagement, although its contribution is relatively smaller compared to discipline. Moreover, work motivation has a significant positive impact on work engagement and mediates the relationship between discipline and work environment with engagement. This indicates that employees' engagement is not only determined by compliance with rules and supportive work conditions but is also strongly influenced by intrinsic and extrinsic motivation. Theoretically, the study reinforces the relevance of the Job Demands–Resources (JD-R) Model and Self-Determination Theory (SDT) in the context of remote work. Practically, the results provide important implications for organizational management in designing discipline policies, creating a supportive work environment, and enhancing employee motivation to strengthen engagement in flexible work arrangements.